Optimization Strategies for Waste Management in Wildlife Tourism Areas: A Systematic Literature Review - Luqman Ash-Shiddiqie; Dwi Nowo Martono; Sri Wahyono (Tecno Scientifica Publishing, 2026)
Waste management in ecologically sensitive tourism areas has faced considerable challenges in balancing operational efficiency with environmental conservation. This study aimed to identify Solid Waste Management (SWM) optimization techniques that had been applied in tourism and conservation areas, evaluate their performance in supporting environmental sustainability, and analyze their respective strengths and limitations. The study employed a Systematic Literature Review (SLR) following the PRISMA guidelines. A total of 22 articles published between 2020 and 2026 were analyzed based on publication characteristics, study locations, optimization techniques, and their contributions to operational efficiency and habitat conservation. The review revealed that SWM optimization techniques had evolved from conventional mathematical approaches toward more integrated models through the adoption of artificial intelligence (AI), the Internet of Things (IoT), waste-to-energy technologies, and circular economy frameworks. Exact optimization models proved effective for cost minimization and transportation optimization, whereas AI and IoT supported real-time monitoring and decision-making. Waste-to-energy and circular economy approaches contributed most significantly to waste reduction, renewable energy generation, and resource recovery. Overall, the review concluded that hybrid optimization models integrating digital technologies, resource recovery, and collaborative governance represented the most promising approach for supporting efficient and sustainable waste management in wildlife conservation tourism areas.